Targeting Neuroinflammation via Purinergic P2 Receptors for Disease Modification in Drug-Refractory Epilepsy - Engel T; Smith J; Alves M (Dove Medical Press, 2021)
Tobias Engel,1,2,* Jonathon Smith,1,2,* Mariana Alves1 1Department of Physiology and Medical Physics, Royal College of Surgeons in Ireland, University of Medicine and Health Sciences, Dublin, D02 YN77, Ireland; 2FutureNeuro, Science Foundation Ireland Research Centre for Chronic and Rare Neurological Diseases, Royal College of Surgeons in Ireland, University of Medicine and Health Sciences, Dublin, D02 YN77, Ireland*These authors contributed equally to this workCorrespondence: Tobias EngelDepartment of Physiology and Medical Physics, Royal College of Surgeons in Ireland, University of Medicine and Health Sciences, 123 St Stephen's Green, Dublin D02 YN77, IrelandTel +353-1-402-5199Fax +35314022447Email tengel@rcsi.ieAbstract: Treatment of epilepsy remains a clinical challenge, with > 30% of patients not responding to current antiseizure drugs (ASDs). Moreover, currently available ASDs are merely symptomatic without altering significantly the progression of the disease. Inflammation is increasingly recognized as playing an important role during the generation of hyperexcitable networks in the brain. Accordingly, the suppression of chronic inflammation has been suggested as a promising therapeutic strategy to prevent epileptogenesis and to treat drug-refractory epilepsy. As a consequence, a strong focus of ongoing research is identification of the mechanisms that contribute to sustained inflammation in the brain during epilepsy and whether these can be targeted. ATP is released in response to several pathological stimuli, including increased neuronal activity within the central nervous system, where it functions as a neuro- and gliotransmitter. Once released, ATP activates purinergic P2 receptors, which are divided into metabotropic P2Y and ionotropic P2X receptors, driving inflammatory processes. Evidence from experimental models and patients demonstrates widespread expression changes of both P2Y and P2X receptors during epilepsy, and critically, drugs targeting both receptor subtypes, in particular the P2Y1 and P2X7 subtypes, have been shown to possess both anticonvulsive and antiepileptic potential. This review provides a detailed summary of the current evidence suggesting ATP-gated receptors as novel drug targets for epilepsy and discusses how P2 receptor-driven inflammation may contribute to the generation of seizures and the development of epilepsy.Keywords: epilepsy, inflammation, purinergic signaling, ATP, P2 receptors, P2X7 receptor, P2Y1 receptor, disease modification, drug refractoriness